Effects of weather variation on a declining population of Slavonian Grebes Podiceps auritus - Ewing, Steven R; Benn, Stuart; Cowie, Neil; Wilson, Lorraine; Wilson, Jeremy D (Journal of ornithology, 2013)
There is an urgent need to develop a detailed understanding of the impacts of climate change on potentially sensitive species of conservation concern. The small population of Slavonian (or Horned) Grebes Podiceps auritus in Scotland has declined markedly in the last two decades in line with predictions of retrospective bioclimatic models. Here, we exploit a long-term, population-wide dataset to investigate the effects of climate variation on key population parameters in this species, and to assess whether climate change has contributed to its decline. Breeding success of Slavonian Grebes in Scotland is low, but a change in breeding success does not appear to account for the population decline. Grebe population parameters were strongly associated with weather conditions during the breeding season, with a positive effect of temperature during the chick period on breeding success and a negative effect of breeding season rainfall on population growth rates. There was, however, no clear evidence linking climate change to the Slavonian Grebe’s decline, with neither of these key weather variables demonstrating long-term directional trends. Despite this, we nevertheless conclude that the potential effects of climate change on Slavonian Grebes cannot be discounted, as climate impacts may be mediated via mechanisms not considered here. Marked recent changes in Slavonian Grebe populations have also been documented in other northern European countries, and we suggest that a priority of future research should be to try to understand the decline of Slavonian Grebes in Scotland in light of these regional scale population dynamics, which might themselves by climate driven.